Are the Public Health Responsibility Deal alcohol pledges likely to improve public health? An evidence synthesis. (26th March 2015) - Knai, Cécile; Petticrew, Mark; Durand, Mary Alison; Eastmure, Elizabeth; Mays, Nicholas
Abstract Aims The English Public Health Responsibility Deal (RD) is a public–private partnership involving voluntary pledges between industry, government and other actors in various areas including alcohol, and designed to improve public health. This paper reviews systematically the evidence underpinning four RD alcohol pledges. Methods We conducted a systematic review of reviews of the evidence underpinning interventions proposed in four RD alcohol pledges, namely alcohol labelling, tackling underage alcohol sales, advertising and marketing alcohol, and alcohol unit reduction. In addition, we included relevant studies of interventions where these had not been covered by a recent review. Results We synthesized the evidence from 14 reviews published between 2002 and 2013. Overall, alcohol labelling is likely to be of limited effect on consumption: alcohol unit content labels can help consumers assess the alcohol content of drinks; however, labels promoting drinking guidelines and pregnancy warning labels are unlikely to influence drinking behaviour. Responsible drinking messages are found to be ambiguous, and industry‐funded alcohol prevention campaigns can promote drinking instead of dissuading consumption. Removing advertising near schools can contribute to reducing underage drinking; however, community mobilization and law enforcement are most effective. Finally, reducing alcohol consumption is more likely to occur if there are incentives such as making lower‐strength alcohol products cheaper. Conclusions The most effective evidence‐based strategies to reduce alcohol‐related harm are not reflected consistently in the RD alcohol pledges. The evidence is clear that an alcohol control strategy should support effective interventions to make alcohol less available and more expensive.